A Study on Biomechanical Models of Sports Bra's Shoulder Straps (Journal of Fiber Bioengineering and Informatics, 2013)
Excessive breast movement causes breast discomfort, pain and sagging. Previous research has shown thatsports bras can support the breasts and reduce breast movement during different activities especiallyrunning. However, so far, no published research has studied the design of shoulder straps from abiomechanical modeling perspective, for improving the performance of sports bras. In this study,biomechanical models of shoulder straps with different widths and in different positions on the shoulderhave been built, based on the assumptions that the behavior of shoulder straps is similar to that ofsprings and the front shoulder strap is aligned with the body. The results show that wider shoulderstraps are more effective in reducing the breast forces, and the location of the shoulder straps on theshoulder affects their performance in controlling breast movement. This provides a theoretical basis foroptimizing the design of shoulder straps to produce more effective sports bras.
Keywords: Shoulder Strap; Sports Bra; Biomechanical Model